Respuesta :
A.
x+y=14
79x+149y=1456
B.
-79(x+y=14)
79x+149y=1456
-79x-79y=-1106
79x+149y=1456
70y=350
y=350/70
y=5
79x+149(5)=1456
79x+745=1456
79x=1456-745
79x=711
x=711/79
x=9
C.
x=-y+14
79(-y+14)+149y=1456
-79y+1106+149y=1456
-79y+149y=1456-1106
70y=350
y=350/70
y=5
x=-y+14
x=-5+14
x=9
D.
9 polyester-fill
5 down-fill
x+y=14
79x+149y=1456
B.
-79(x+y=14)
79x+149y=1456
-79x-79y=-1106
79x+149y=1456
70y=350
y=350/70
y=5
79x+149(5)=1456
79x+745=1456
79x=1456-745
79x=711
x=711/79
x=9
C.
x=-y+14
79(-y+14)+149y=1456
-79y+1106+149y=1456
-79y+149y=1456-1106
70y=350
y=350/70
y=5
x=-y+14
x=-5+14
x=9
D.
9 polyester-fill
5 down-fill
Answer:
A.
x 79 + y149=1456
x +y = 14
B.
multiplying the second equation by 79 and subtracting it to the first equation.
C.
Solving for x in the second equation and Replacing x in the first equation, then solve for y.
D.
Down-fill sleeping bags(y) = 5
Polyester-fill sleeping bags (x) =9
Step-by-step explanation:
Hi, the sum of the product of each type of sleeping bag multiplied by its cost is equal to 1456 (equation1)
The sum of both sleeping bags sold is equal to 14 (equation 2)
A.
x 79 + y149=1456
x +y = 14
B. multiplying the second equation by 79 and subtracting it to the first equation.
79x + y149=1456
-
79x +79y = 1106
_____________
70y = 350
y = 350/70
y = 5
C. solving for x in the second equation:
x = 14-y
Replacing x in the first equation:
79 (14-y)+ 149y=1456
1106-79y +149y =1456
149y-79y = 1456-1106
70y =350
y = 350/70
y = 5
D:
Replacing the value of Y in any equation:
x +y = 14
x+ (5) =14
x =14-5
x = 9
Down-fill sleeping bags(y) = 5
Polyester-fill sleeping bags (x) =9